Constellations of firms and new ventures - Lorenzoni, Gianni; Ornati, Oscar A. (Journal of Business Venturing, 1988)
Firm growth is typically described as, “from the inside out;” an integrated process of resource capture. Supplementing the traditional view of growth from within, this article focuses on how small firms come into being and grow resorting to cooperative relationships with external organizations. Through such a process new firms come into being without notable direct investments and grow without significant employment increases. The emerging organizational design stresses the importance of constellations. Constellational structures suggest that organizations do not survive as isolated and self-sufficient entities; rather they are strongly tied to supportive quasi-infrastructural collectives. Firms grow through various and changing interorganizational relationships. We suggest that a growth path of firm disintegration is positively associated with flexibility, cost reductions and more favorable competitive position; that the success of this path in different industries and countries makes a venturing without investing process more than a “small is beautiful fad”. We find regularities in growth patterns, at the beginning, an unplanned constellation of firms each geared to solving short-term contingent problems. Planned interfirm linkages and partnerships geared to greater effectiveness arise in more advanced stages: in this manner the competitive position of the constellation is improved. This article suggests underlying conditions facilitating the growth of organizations that use synergies and the constellations' resources effectively.